Auditing, An Introduction to the Work of the Public Accountant (Book). - Myers, John H.; Cannon, Arthur M. (The Accounting Review, 1954)
Reviews the book "Auditing, an Introduction to the Work of the Public Accountant," by Eric L. Kohler.